PERBEDAAN TINGKAT KELELAHAN KERJA ANTARA TENAGA KERJA TANPA MAKAN PAGI DAN DENGAN MAKAN PAGI - Risma Arum Lintar Indira; Ida Wahyuni; Daru Lestantyo Lestantyo (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2012)
ABSTRACK Fatigue is a condition of the weakening force to perform an activity. It is known that the workers were not given breakfast by the company with working hours that began at 07.00 WITA. From interviews with 7 workers from the putty section, 3 are not used to get breakfast and 4 workers drink milk as a substitute for breakfast because pressed for time. workers also feel fatigue that is easy to sleepy, dizziness in the head, thirsty and stiffness in the shoulder, hand and arm. Breakfast can prevent energy deficiency that can cause fatigue. The purpose of this study is to analyze the differences in fatigue before and after breakfast. This research using an explanation of research with quasi-experimental research methods and one group pretest-posttest as study design. The population in this study were female workers of putty section in PT. Sumalindo Lestari Jaya Tbk with the total number of samples is 17 people total population. Analysis of data using Paired T-test bivariate analysis to know the difference between the two samples associated with a significant level p <0.05. The results of this study showed difference in fatigue without breakfast and with breakfast. Paired T-test test statistically results obtained significant values ​​with p = 0.001 (p <0.005). The conclusion of this study is that there are different degrees of fatigue without breakfast and with breakfast on female workers in putty section. Keywords : fatigue, breakfast, woman worker’s Kesmasindo. Volume 5(2) Juli 2012, hlm. 191- 202